Experimental and Investigational Targeted Therapies for the Management of Fibrosis in NASH: An Update - Huisman TM; Dieterich DT; Friedman SL (Dove Medical Press, 2021)
Tsipora M Huisman, Douglas T Dieterich, Scott L Friedman Division of Liver Diseases, Icahn School of Medicine at Mount Sinai, New York, NY, USACorrespondence: Scott L FriedmanIcahn School of Medicine at Mount Sinai, Box 1123, 1425 Madison Ave, Room 1170C, New York, NY, 10025, USAEmail Scott.friedman@mssm.eduAbstract: There have been major advances in the treatment of HBV and HCV with anti-viral treatments, which is reducing the prevalence of fibrosis due to these viruses and obviating the need for anti-fibrotic therapies in these diseases. At the same time, however, the prevalence of non-alcoholic fatty liver disease (NAFLD) has been increasing, of which a substantial fraction of patients have non-alcoholic steatohepatitis (NASH), which may progress to cirrhosis. Accordingly, NASH is emerging as the leading indication for liver transplantation in North America and Europe. Progress in uncovering pathogenic determinants of fibrosis in NASH include metabolic dysregulation in hepatocytes that induce inflammation and cytokine secretion leading to cell injury and apoptosis, among others. These pathogenic events converge upon hepatic stellate cells, which are the primary fibrogenic cell in liver, and represent a target of new therapeutic candidates that are currently being evaluated in animal models and clinical trials. This review highlights key experimental and investigational therapies for NASH fibrosis, whose evaluation will be accelerated as new non-invasive markers of fibrosis are established. While no drugs are approved yet for NASH fibrosis, there is growing optimism that new pharmacotherapies are likely to emerge within the next 3 years that will favorably alter the natural history of disease.Keywords: liver fibrosis, novel treatments, NASH, pharmacotherapies, antifibrotic therapy, cirrhosis, hepatic stellate cell